Evaluation of Some Toxic and Essential Trace Elements in Children Foods and Infant Formulae by Using ICP-OES - Elsheikh, Malik A.; Ali, Dafaalla M.H.; Alotaibi, Saad H. (Asian Journal of Chemistry, 2020)
In Turabah province of Saudi Arabia, infant formula and children′s food products were investigated to determine the concentrations of essential trace elements, namely Mn, Ni, V and Si, and toxic trace elements, namely Al, Ba, Pb, Cd, and As, present in them. Their daily intake amounts were calculated and compared with provisional tolerable daily intake (PTDI), which was calculated based on the provisional tolerable weekly intake (PTWI), which was recommended by joint FAO/WHO. The results obtained were found to be below the PTDI levels. Some samples exhibited a large amount of Al. The PTWI of Si and V is not established; however, their concentrations were compared with those reported in other studies. In some samples, a high concentration of Si was observed. The method employed for evaluation was based on the limit of quantification (LOQ), limit of detection (LOD), and recovery percent of 92.3–101.6%. Accuracy and precision were employed for evaluating the results.